Design and Control Optimization of Compensation Mechanism of Crystallizer Automatic Slag Adding Machine - Ge Jun; Chen Xinyuan; Lu Yongliang (Jixie chuandong)
Aiming at the problems such as the loss of mold powder and the uneven thickness of the mold powder,the automatic slag adding machine with rectangular rectification compensation mechanism is designed to solve the problem of slag wasting. The kinematics model of the mechanism is established,and the angular velocity of the driving link is simulated by MATLAB. The appropriate electronic control command curve is fitted and adjusted in real time to ensure that the central speed of the discharge port is basically stable,which is to solve the uneven problem. Finally,the experimental results show that the error of displacement of the sliding platform between the measured value and the theoretical value is less than 5%. The central trajectory of the discharge port is approximately straight and the swing speed is basically the same. The distribution of the mold powder in the mold is uniform.